INTERACTIVE VISUALIZATION OF LARGR-SCALE 3D SCATTERED DATA FROM A TSUNAMI SIMULATION - Zhao, Kun; Sakamoto, Naohisa; Koyamada, Koji; Tanaka, Satoshi; Murotani, Kohei; Koshizuka, Seiichi (International Journal of Industrial Engineering: Theory, Applications and Practice, 2017)
Recently, more and more scientific simulation fields generate large-scale three-dimensional (3D) scattered data. To observe the internal information, interactive visualization technique to extract the internal information of such data is always needed. However, due the highly complex distribution and structure, interactive visualization of such data is a very challenging work. Moreover, the simulation result is also time-varying, which makes the visualization more difficult. In this work, we are focusing on a large-scale 3D scattered data, which are generated from a tsunami (tidal wave) simulation. We visualize the large-scale 3D scattered data by developing an interactive particle-based rendering (IPBR) method. A main feature of the proposed IPBR method is to implement a semi-transparent effect using ensemble average for the particles so that the volume rendering effect to observe the internal information for the 3D scattered data can be realized. Moreover, the real time adjustment of the transfer function is also implemented by changing the particle radius and particle color. We calculate the density of the 3D point data and adjust the point radius by a resizing function. Further, we also develop a time-varying rendering mechanism to render the temporal behaviors of the time-varying data. As the application to the tsunami simulation data, the experimental results show that the detailed analysis of the spatial and temporal features of the tsunami can be facilitated well with the proposed technique.